To Treat or Not to Treat?: Exploring Factors Influencing Intravenous Thrombolysis Treatment Decisions for Minor Stroke. Issue 8 (August 2018) - Levine, Steven R.; Weingast, Sarah Z.; Weedon, Jeremy; Stefanov, Dimitre G.; Katz, Patricia; Hurley, Dana; Kasner, Scott E.; Khatri, Pooja; Broderick, Joseph P.; Grotta, James C.; Feldmann, Edward; Panagos, Peter D.; et al.
Abstract : Background and Purpose—: The 2015 updated US Food and Drug Administration alteplase package insert altered several contraindications. We thus explored clinical factors influencing alteplase treatment decisions for patients with minor stroke. Methods—: An expert panel selected 7 factors to build a series of survey vignettes: National Institutes of Health Stroke Scale (NIHSS), NIHSS area of primary deficit, baseline functional status, previous ischemic stroke, previous intracerebral hemorrhage, recent anticoagulation, and temporal pattern of symptoms in first hour of care. We used a fractional factorial design (150 vignettes) to provide unconfounded estimates of the effect of all 7 main factors, plus first-order interactions for NIHSS. Surveys were emailed to national organizations of neurologists, emergency physicians, and colleagues. Physicians were randomized to 1 of 10 sets of 15 vignettes, presented randomly. Physicians reported the subjective likelihood of giving alteplase on a 0 to 5 scale; scale categories were anchored to 6 probabilities from 0% to 100%. A conjoint statistical analysis was applied. Results—: Responses from 194 US physicians yielded 156 with complete vignette data: 74% male, mean age 46, 80% neurologists. Treatment mean probabilities for individual vignettes ranged from 6% to 95%. Treatment probability increased from 24% for NIHSS score =1 to 41% for NIHSS score =5. The conjoint model accounted for 25% of total observed response variance. In contrast, a model accounting for all possible interactions accounted for 30% variance. Four of the 7 factors accounted jointly for 58% of total relative importance within the conjoint model: previous intracerebral hemorrhage (18%), recent anticoagulation (17%), NIHSS (13%), and previous ischemic stroke (10%). Conclusions—: Four main variables jointly account for only a small fraction (<15%) of the total variance related to deciding to treat with intravenous alteplase, reflecting high variability and complexity. Future studies should consider other variables, including physician characteristics. Abstract : Supplemental Digital Content is available in the text.